Réponses

2014-01-01T00:30:54+01:00
Ex 1
(1^{-5})^{5+3} = (1) ^{5+3} = 4

( 5^{-5})(3 +  2^{5} ) = ( \frac{1}{3125})(35) =  \frac{7}{625}   ≈0,0112

(3 -  5^{5}) - (8 +  5^{5})= (- 3 132) - ( 3 133) = - 6255

(2^{-5}) - ( 1 -  2^{5}) = ( \frac{1}{32}) - (-31) =  \frac{993}{32}  ≈31,03125

Ex 2


A. ( 3^{3-2})( 1^{3}) = (25)(1)=25
B. (2^{3} )(-1+2^{3})= (8) (7) = 56
C. (2^{2-3})(3^{2+7}) = (1)(16)=16
D.(1 + 2^{3})(2 + 5^{3})=(9)(127)=1 143

Vérifie mes calculs, une erreur est si vite arrivée...
Bonne Année 2014 !